Identification of factors and outcomes of obstetric patients in the surgical intensive care unit of a tertiary care hospital - Ahmed, Hubba; Batool, Zaira; Perchani, Ashok; Sultan, Syed Farjad (Bangladesh Journal of Medical Science, 2025)
Background Despite of massive development in health sciences, maternal mortality in Pakistan is still highest in Southeast Asia. Derailment of widespread physiological changes or evolution of any highrisk pregnancy induced condition may necessitate admission to an intensive care unit (ICU) during the course of pregnancy or postpartum. The purpose of this study is to identify the factors leading to ICU admissions and outcomes of obstetric patients in surgical ICU of a tertiary care hospital. Methods A descriptive study was conducted in Department of Anaesthesiology, the Surgical ICU and Pain Management, Civil Hospital Karachi for 6 months from June to December 2022.A Total 138 patients with antepartum and postpartum conditions requiring ICU admission were recruited in this study. All demographic details were recorded in a predesigned proforma. The patient’s parturient status as antepartum or postpartum and the comorbidities with which they presented were recorded. Results Patients’ mean age was 26.68 ± 5.67 years. Hypertensive disorder was the commonest factor (51.45%) leading to ICU admission followed by obstetric hemorrhage 37.86% and sepsis was observed in 10.87%. There were 15.94% (22 of 138) women who were expired and 81.06% (116 of 18) were discharged from surgical ICU. Mortality rate was significantly high in those women whose causes were obstetric hemorrhage and sepsis. (p=0.0005). Conclusion The most frequent cause of ICU admission was the hypertensive condition of pregnancy, which was followed by obstetric hemorrhage and infection. It is essential to approach these patients meticulously and embark on rapid management protocol with a team approach to save these precious lives. BJMS, Vol. 24 No. 03 July’25 Page : 807-814